Patterns of Postoperative Visits Among Medicare Fee-for-service Beneficiaries. Issue 6 (June 2020) - Kranz, Ashley M.; Mulcahy, Andrew; Ruder, Teague; Lovejoy, Susan; Mehrotra, Ateev
Abstract : Objective: To describe patterns of postoperative visits reported for Medicare fee-for-service (FFS) patients. Background: Payment for most surgical procedures bundles postoperative visits within a global period of either 10 or 90 days after a procedure. There is concern that payments for some procedures are excessive because the number of postoperative visits provided is less than the number of postoperative visits used to help determine payment. To obtain data to inform this concern, Medicare required select surgeons to report on their postoperative visits starting July 1, 2017. Methods: We analyzed Medicare FFS claims data from surgeons who billed Medicare for 1 or more of the 293 common procedure codes between July 1, 2017 and December 31, 2017 in the 9 states where surgeons were required to report postoperative visits. We examined the share of procedures with any reported postoperative visits and the proportion of expected postoperative visits provided. To address concerns about underreporting, we also examined procedures performed by a subset of surgeons actively reporting postoperative visits. Results: We linked 663, 681 procedures to 422, 432 postoperative visits. The share of procedures with any postoperative visits was higher for procedures with 90-day global periods (70.1%) than for procedures with 10-day global periods (3.7%). The proportions of expected postoperative visits provided for 90-day global and 10-day global periods were 0.37 and 0.04 respectively. Among surgeons actively reporting postoperative visits, the proportions of expected postoperative visits provided were modestly higher (procedures with 90-day global periods=0.46 and 10-day global periods=0.16). Conclusions: The proportion of expected postoperative visits that were provided is low. These results support the need for a reassessment of payment for surgical procedures. Abstract : Supplemental Digital Content is available in the text